2015
DOI: 10.1038/ncomms9596
|View full text |Cite
|
Sign up to set email alerts
|

Observation of correlated electronic decay in expanding clusters triggered by near-infrared fields

Abstract: When an excited atom is embedded into an environment, novel relaxation pathways can emerge that are absent for isolated atoms. A well-known example is interatomic Coulombic decay, where an excited atom relaxes by transferring its excess energy to another atom in the environment, leading to its ionization. Such processes have been observed in clusters ionized by extreme-ultraviolet and X-ray lasers. Here, we report on a correlated electronic decay process that occurs following nanoplasma formation and Rydberg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
4
29
0
Order By: Relevance
“…New experimental findings confirm that during the cluster expansion excited atomic states can relax by autoionization2526. Alternatively, ICD or a process involving a quasi-free nanoplasma electron can take place27. In superfluid He nanodroplets28 autoionization might also be caused by collisions of excited atoms and is referred to as a Penning ionization29.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…New experimental findings confirm that during the cluster expansion excited atomic states can relax by autoionization2526. Alternatively, ICD or a process involving a quasi-free nanoplasma electron can take place27. In superfluid He nanodroplets28 autoionization might also be caused by collisions of excited atoms and is referred to as a Penning ionization29.…”
mentioning
confidence: 88%
“…In superfluid He nanodroplets28 autoionization might also be caused by collisions of excited atoms and is referred to as a Penning ionization29. To account for a broad family of electron correlation processes that may take place in clusters, a general term - correlated electronic decay (CED) - was introduced27. The CED term describes energy exchange between at least two Rydberg electrons which are located either within the same doubly excited atom (autoionization) or between electrons located in different atoms (ICD or Penning ionization).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2(b). The population by the XFEL pulse of the neutral excited states is expected to deplete by a variant of the interatomic Coulombic decay (ICD) [26] in which two excited atoms exchange energy ionizing one of them and deexciting the other [27][28][29][30] [see Fig. 2(b)].…”
Section: B Xe Clustersmentioning
confidence: 99%
“…The time constant of the ICD process depends on the excited states involved, on the distance between the excited atoms, and on their number, being thus rather difficult to estimate from first principles for the present conditions. However, a number of theoretical and experimental studies have shown [27][28][29][30][31][32] that the timescale of ICD in rare-gas clusters is typically a few hundred femtoseconds. Therefore, the present extracted averaged time constant of ∼250 fs is fully within the range of timescales to be expected for ICD mechanisms in such systems.…”
Section: B Xe Clustersmentioning
confidence: 99%